1992
DOI: 10.1164/ajrccm/146.1.109
|View full text |Cite
|
Sign up to set email alerts
|

Allergic and Nonallergic Asthmatics Have Distinct Patterns of T-Cell Activation and Cytokine Production in Peripheral Blood and Bronchoalveolar Lavage

Abstract: Activation of lymphocyte subpopulations was determined in conjunction with levels of cytokines in peripheral blood and bronchoalveolar lavage (BAL) of asthmatics. Allergic asthmatics had increased numbers of CD4+ IL-2R+ T cells in peripheral blood and BAL, and T-cell activation closely correlated with numbers of low-affinity IgE receptor (CD23) bearing B cells. In contrast, in nonallergic asthmatics both CD4+ and CD8+ T cells from blood and BAL had increased expression of IL-2R, HLA-DR, and VLA-1. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
410
5
11

Year Published

1996
1996
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 736 publications
(454 citation statements)
references
References 10 publications
28
410
5
11
Order By: Relevance
“…The reports of increased IL-5 protein levels in the BAL fluid, serum and peripheral blood T cell supernatants of asthmatics (Walker et al 1992, Motojima et al 1993, support the findings of increased numbers of IL-5 mRNA positive cells in these biological fluids. In addition, T cell lines that have been established from the BAL fluid and peripheral blood of atopic asthmatics secrete increased levels of IL-5 compared to atopic and non-atopic controls, thus providing further evidence that T cells in asthma have a propensity to make both IL-5 mRNA transcripts and IL-5 translated product which can then activate eosinophils (Endo et al 1993, Okudaira et al 1995, Till et al 1995.…”
Section: Asthma and Il-5 Human Studies: Il5 Mrna And Proteinsupporting
confidence: 73%
See 1 more Smart Citation
“…The reports of increased IL-5 protein levels in the BAL fluid, serum and peripheral blood T cell supernatants of asthmatics (Walker et al 1992, Motojima et al 1993, support the findings of increased numbers of IL-5 mRNA positive cells in these biological fluids. In addition, T cell lines that have been established from the BAL fluid and peripheral blood of atopic asthmatics secrete increased levels of IL-5 compared to atopic and non-atopic controls, thus providing further evidence that T cells in asthma have a propensity to make both IL-5 mRNA transcripts and IL-5 translated product which can then activate eosinophils (Endo et al 1993, Okudaira et al 1995, Till et al 1995.…”
Section: Asthma and Il-5 Human Studies: Il5 Mrna And Proteinsupporting
confidence: 73%
“…In addition, the increased expression of IL-5 mRNA in BAL has been directly correlated to asthma symptom severity and inversely correlated to abnormal airway physiology ). Finally, in the studies where increased IL-5 protein levels were demonstrated in the BAL fluid, serum and peripheral blood T cell supernatants (Walker et al 1992, Motojima et al 1993 of asthmatic subjects, the IL-5 protein levels detected correlated with the numbers of eosinophils present in these fluids (Walker et al 1992).…”
Section: Asthma and Il-5 Human Studies: Il5 Mrna And Proteinmentioning
confidence: 90%
“…Previous studies have reported that BAL concentrations of IL-4 and IL-5 protein were similar in asthmatic and healthy subjects [27], while others have reported increased IL-4 and IL-5 protein concentrations in BAL fluid and in culture supernatants from PB and BAL T cells of allergic asthmatics as compared to normal subjects [3]. This is not necessarily inconsistent with our findings, but could reflect increased production of Th2 cytokines by small numbers of cells in each compartment, rather than an increased number of Th2-cytokine producing T cells.…”
Section: Discussionmentioning
confidence: 90%
“…T lymphocytes have been suggested to play an important role in regulating the inflammatory and immunological processes thought to underlie asthma [2], by manufacturing and releasing an array of cytokines and chemokines [2,3]. In particular, interferon-gamma (IFN-g) has many proinflammatory activities on endothelium and eosinophils [4,5], IL-4 and IL-13 promote isotype switching of B-lymphocytes towards IgE production and IL-5 is the main cytokine regulating the differentiation and activation of eosinophils [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In experimented studies, in serum of mice exposed to diisocyanates by inhalation not only total IgE but also specific IgE, IgG and IL-2, 4, 5, and IFNγ were increased [58][59][60][61] . Inflammatory cell infiltrates in bronchial biopsies of patients suffering from isocyanate induced asthma include mast cells, eosinophils, and activated lymphocytes (bearing the IL-2 receptor (CD25)) 62,63) . The presence of activated lymphocytes and eosinophils in bronchial biopsies suggest that a T lymphocyte eosinophil interaction may be important in asthma of different origin, a hypothesis further supported by the finding of the cells expressing IL-5 messenger RNA in bronchial biopsies of asthmatics.…”
Section: Immunological Mechanisms and Clinical Responsesmentioning
confidence: 99%